Konsep Kemanusiaan dalam Pemikiran Tafsir Sayyid Qutb: Analisis Tematik atas Fi Zilal al-Qur'an - M. Ma’rufukurhi; M. Mukhid Mashuri; Nyoko Adi Kuswoyo; Ahmad Zainuddin (JOM, 2026)
Sayyid Qutb’s thought is often reduced to political discourse and radical movements, thereby obscuring his intellectual contribution to the discourse on humanity (Islamic humanism). This study aims to reconstruct the concept of humanity according to Sayyid Qutb through his magnum opus, Fi Zilal al-Qur’an. Employing a library research method and a thematic (maudhu‘i) exegetical approach, this study inventories Qur’anic verses related to the concept of human beings and analyzes Qutb’s interpretations of these verses. The findings reveal that Qutb’s concept of humanity is fundamentally grounded in the principle of tawhid. The essence of the human being is shaped by the integration of material elements derived from clay and a spiritual dimension originating from the divine spirit. Human dignity (karamah insaniyyah) is manifested through free will and a dual responsibility as both khalifah (vicegerent on earth) and ‘abd (servant of God). Furthermore, Qutb emphasizes that equality and universal brotherhood cannot be achieved under secular materialistic systems, but only through complete submission to the divine order (hakimiyyah). This study engages with various previous local studies and concludes that Qutb’s thought offers both a critical perspective and a paradigmatic solution to the modern crisis of humanity, which is marked by dehumanization resulting from the dominance of capitalism and materialism.